Impressionism - Brooks, Susie (Brooks, Susie. Inside art movements., 2020)
Presents a brief visual overview of the Impressionism art movement, covering its history, various expressions of the movement, important works of art, and famous artists. Includes a timeline, a glossary, and further resources.